Рец. на книгу: Микола Жулинський. Моя Друга світова: роман-хроніка в голосах. – К, : Ярославів Вал, 2016. – 416 с. - Каліщук, Оксана (Літопис Волині, 2017)
Рец. на книгу: Микола Жулинський. Моя Друга світова: роман-хроніка в голосах. – К, : Ярославів Вал, 2016. – 416 с.